2000
DOI: 10.1016/s0896-6273(00)00072-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Response Variability in Simultaneously Recorded Retinal, Thalamic, and Cortical Neurons

Abstract: The response of a cortical cell to a repeated stimulus can be highly variable from one trial to the next. Much lower variability has been reported of retinal cells. We recorded visual responses simultaneously from three successive stages of the cat visual system: retinal ganglion cells (RGCs), thalamic (LGN) relay cells, and simple cells in layer 4 of primary visual cortex. Spike count variability was lower than that of a Poisson process at all three stages but increased at each stage. Absolute and relative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
364
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(425 citation statements)
references
References 58 publications
(9 reference statements)
48
364
3
1
Order By: Relevance
“…While it is frequently assumed that cortical neurons can be modeled by Poisson processes with a refractory period (Shadlen and Newsome 1998;Kara et al 2000) due to their high variability (Softky and Koch 1993), this view is being challenged more and more (Engel et al 2008;Farkhooi et al 2009;Maimon and Assad 2009). In particular, recent studies have found that cortical neurons could display nonrenewal spike train statistics in vivo (Engel et al 2008).…”
Section: Universality Of Nonrenewal Spike Train Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is frequently assumed that cortical neurons can be modeled by Poisson processes with a refractory period (Shadlen and Newsome 1998;Kara et al 2000) due to their high variability (Softky and Koch 1993), this view is being challenged more and more (Engel et al 2008;Farkhooi et al 2009;Maimon and Assad 2009). In particular, recent studies have found that cortical neurons could display nonrenewal spike train statistics in vivo (Engel et al 2008).…”
Section: Universality Of Nonrenewal Spike Train Statisticsmentioning
confidence: 99%
“…Such a description assumes that the spiking activity can be described by renewal process where all memory is erased after each action potential firing (Cox and Lewis 1966). The Poisson process is, perhaps, the best-known example of a renewal process: it is characterized by an exponential distribution of ISIs and has been frequently used to describe the firing of cortical neurons (Shadlen and Newsome 1998;Kara et al 2000). There is, however, accumulating evidence that the spiking activities of many neurons are not well described by renewal processes as they display memory in their spiking activity that persists over multiple action potential firings (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical studies reported that FFs change with stimulus due to negative correlations between FF and firing rate (6,39), whereas stimulus-dependent changes of trial-by-trial variability have only been observed in the midbrain and thalamus (40,41). Variations of noise correlations with respect to speed of moving targets and movement direction have been reported in pairs of MT and motor-cortical neurons, respectively (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the degree of precision of spiking in response to repeated presentations of the same stimulus appears to decrease along the visual pathway 50 , whereas spike-count variability increases 42,43,47,[51][52][53] . This could be due to the presence of background cortical activity, in which case a method to uncover the stimulus-locked precision is needed (FIG.…”
Section: Evidence For Spike-time Precision In the Visual Systemmentioning
confidence: 97%